Determination of vitamin K1 using square wave adsorptive stripping voltammetry at solid glassy carbon electrode - Sýs, Milan; Jashari, Granit; Švecová, Blanka; Tahir, Arbneshi; Metelka, Radovan (My University, 2018)
A new electroanalytical method for determination of phylloquinone (vitamin K1) occuring in food samples of plant origin has been developed. Presented method is based on adsorptive accumulation of this biologically active compound onto the surface of solid glassy carbon electrode with subsequent electrochemical detection using square wave adsorptive stripping voltammetry in 0.1 M HCl. Two linear ranges of phylloquinone determination were 1.0 x 10(-8)-1.0 x 10(-6) mol L-1 and 5.0 x 10(-6)-1.0 x 10(-4) mol L-1 with the detection limits of 8.9 x 10(-9) and 5.1 x 10(-8) mol L-1, respectively. Obtained results have shown that square wave voltammetry with adsorptive accumulation step is very sensitive method for the determination of vitamin K-1, being comparable to standard high performance liquid chromatography method for food analysis (EN 14148:2003).
Stanovení vitamínu K1 pomocí adsorptivní rozpouštěcí square wave voltametrie na elektrodě ze skelného uhlíku
Keywords: Glassy carbon electrode; square wave voltammetry; vitamin K1; phylloquinone; food analysis; Elektroda ze skelného uhlíku; square wave voltametrie; vitamín K1; filochinon; analýza potravin